Duration of family bonds of Brent Geese Branta bernicla on the Pacific coast of North America - Reed, Austin (Wildfowl, 1993)
During the course of field investigations along the coasts of British Columbia and Washington State over the fall, winter and spring 1987-88, I observed 147 groups of Brent Geese which behaved as family units. Another five such groups were observed and confirmed as genuine families based on records of their coded leg rings. Further observations of marked broods whose codes could not be read provided additional evidence of the maintenance of family bonds through the winter and into early spring. This is in contrast with an earlier report which indicated that Brent Goose family bonds disintegrated during fall staging on the Alaskan Peninsula; the contradiction probably arises from the difficulty of recognizing the relatively infrequent and subtle forms of family associations in the dense concentrations of Brent Geese which occur at staging and wintering areas. Brent Geese appear to have a social system in which overt display of family ties emerges only infrequently when broods compete for some secondary, patchily distributed food source or roost site. This system allows Brent Geese to benefit, on the one hand, from the advantages of flock feeding (vigilance, information on food availability, etc.,) without disruption from conspecifics while feeding over broad, dense Zostera meadows and, on the other, to deploy aggressive behavior to confer increased feeding opportunities on brood members when a patchily distributed food source is exploited. Unattended juveniles occur in the flock, possibly as a consequence of the relative infrequency with which close family ties are expressed.